Modeling of the enterprise functioning stability using the automatic control theory apparatus - Guryanova, L.; Nikolaiev, I.; Zhovnovach, R.; Milevskiy, S.; Ivakhnenko, O.; Panasenko, O.; Prokopovych, S.; Chagovets, L.; Vasylenko, D.; Rudachenko, O.; Гур’янова, Л. С.; Ніколаєв, І. В.; et al. (PC Technology Center, 2017)
The necessity of using new forms of production organization and estimating the enterprise functioning stability in dynamics is substantiated. A complex of economic-mathematical models for estimation and analysis of the enterprise functioning stability in crisis conditions, using the logistic approach and the systems automatic control theory apparatus is proposed. A simulation model for assessing the enterprise functioning stability was constructed. Обґрунтовано необхідність використання нових форм організації виробництва та оцінки стійкості функціонування підприємств у динаміці. Запропоновано комплекс економіко-математичних моделей оцінки й аналізу стійкості функціонування підприємства в кризових умовах, що використовують логістичний підхід та апарат теорії автоматичного управління системами. Побудовано імітаційну модель оцінки стійкості функціонування підприємства. Обоснована необходимость использования новых форм организации производства и оценки устойчивости функционирования предприятий в динамике. Предложен комплекс экономико-математических моделей оценки и анализа устойчивости функционирования предприятия в кризисных условиях, используют логистический подход и аппарат теории автоматического управления системами. Построена имитационная модель оценки устойчивости функционирования предприятия.
Моделювання стійкості функціонування підприємства з використанням апарату теорії автоматичного управління
Моделирование устойчивости функционирования предприятия с использованием аппарата теории автоматического управления
Keywords: functioning stability; structural model; simulation model; production and sales system; automatic control theory; стійкість функціонування; структурна модель; імітаційна модель; виробничо-збутова система; теорія автоматичного управління; устойчивость функционирования; структурная модель; имитационная модель; производственно-сбытовая система; теория автоматического управления